The Prevalence of and Factors Associated With Anxiety and Depression Among Working-Age Adults in Mainland China at the Early Remission Stage of the Coronavirus 2019 Pandemic - Xie, Haixia; Huang, Xiaowei; Zhang, Qi; Wei, Yan; Zeng, Xuheng; Chang, Fengshui; Wu, Shuyin (Frontiers in Psychology, 2022)
Background: The COVID-19 outbreak has led to a considerable proportion of adverse psychological symptoms in different subpopulations. This study aimed to investigate the status of anxiety and depression and their associated factors in the adult, working-age population in Mainland China at the early remission stage of the COVID-19 pandemic. Methods: An online study was conducted among 1863 participants in 29 provinces in Mainland China from March 23 to 31, 2020. Their mental health was evaluated by the Generalized Anxiety Disorder scale (GAD-7) and the Patient Health Questionnaire (PHQ-9). Descriptive analysis, Chi-square, and multiple logistic regressions were applied. Results: 44.5% of the participants had anxiety, 49.2% had depression, and 37.9% showed a combination of depression and anxiety. 83.7% of the participants claimed that the pandemic had a negative impact on their medical needs, which was the primary predictor of mental health, the degree of impact being positively related to the prevalence of anxiety and depression. More chronic diseases, moderate to bad self-rated health, severe perceived infection risk, and younger age group were the common risk factors for anxiety and depression. Having no children, unemployment, and a college-level educational background were associated with a higher anxiety prevalence, whereas unmarried participants were correlated with a higher depression prevalence. Conclusions: The working-age population showed a relatively high risk of anxiety and depression in Mainland China at the early remission stage of the pandemic. To improve medical services capacity for routine and delayed medical service needs should be a part of policy-makers’ priority agenda during this period of crisis.